Louise Duchesneau and Wolfgang Marx (eds), György Ligeti: Of Foreign Lands and Strange Sounds (2011) - Morse, Daniel (Journal of the Society for Musicology in Ireland, 2014)
A review of Louise Duchesneau and Wolfgang Marx (eds), György Ligeti: Of Foreign Lands and Strange Sounds (Woodbridge: The Boydell Press, 2011). ISBN 978-1-84383-550-9.